A Textbook of fluid mechanics and hydraulic machines - Bansal, R.K (Laxmi Pub, 2002)
A Textbook of fluid mechanics and hydraulic machines / Bansal, R.K.. -- New Delhi: Laxmi Pub., 2002 532 B212e8 8th ed. No. of Copies : 1